2010
DOI: 10.1152/ajprenal.00216.2010
|View full text |Cite
|
Sign up to set email alerts
|

Mice lacking the matrix metalloproteinase-9 gene reduce renal interstitial fibrosis in obstructive nephropathy

Abstract: . Mice lacking the matrix metalloproteinase-9 gene reduce renal interstitial fibrosis in obstructive nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
85
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 37 publications
7
85
0
4
Order By: Relevance
“…In the current study, we showed that inhibition of MMP-9 activity by an MMP-2/9 inhibitor or MMP-9 Ab, specifically at early or late stages of UUO, was protective against the development of renal fibrosis. This result is consistent with a role of MMP-9 in renal fibrosis, which was previously reported, 19,39 however the mechanism underlying its contribution was not fully explained. To the best of our knowledge, our study is the first to demonstrate a stage-specific expression of MMP-9 in renal fibrosis and its relevance to stage-specific therapy.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the current study, we showed that inhibition of MMP-9 activity by an MMP-2/9 inhibitor or MMP-9 Ab, specifically at early or late stages of UUO, was protective against the development of renal fibrosis. This result is consistent with a role of MMP-9 in renal fibrosis, which was previously reported, 19,39 however the mechanism underlying its contribution was not fully explained. To the best of our knowledge, our study is the first to demonstrate a stage-specific expression of MMP-9 in renal fibrosis and its relevance to stage-specific therapy.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies by Yang et al 19,39 demonstrated that direct or indirect inhibition of MMP-9 activity resulted in a reduction in tubular cell EMT and renal fibrosis in obstructive nephropathy. Findings from our current study further extended those observations where early-and latestage inhibition of MMP-9 not only reduced tubular cell EMT and renal fibrosis but also reduced MMP-9-cleaved OPN and macrophage infiltration.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…With regard to MMP-9, a recent study demonstrated that mice lacking the MMP-9 gene show mild renal interstitial fibrosis in unilateral ureteral obstruction (UUO). 22 However, the therapeutic effect of MMP-2 inhibition on progressive renal fibrosis is still uncertain.…”
mentioning
confidence: 99%
“…1 Metabolize dysfunction of MMP-9 was reported to take part in the pathogenesis of renal diseases. [2][3][4] The homeostasis of ECM is destroyed, which is an important characteristic of renal diseases. MMP-9 is one of the most important MMPs for the ECM degradation.…”
Section: Introductionmentioning
confidence: 99%